Assessment Mechanism for Educators at Aisyiyah Tembung Special Needs School - Deliati; Yenti Arsini; Robbi Asri; Zadrian Ardi (Universitas PGRI Yogyakarta, 2026)
Inclusive education has become a global priority, emphasizing the right of children with special needs (CSN) to receive quality education without discrimination. This study is motivated by the critical role of accurate assessment in designing effective learning for children with special needs (CSN). This research aims to evaluate the implementation of educational assessment for CSN at Aisyiyah Tembung Special Needs School and to identify the factors influencing its practice. A qualitative approach was employed, using content analysis of verbal, visual, and written documentation. The research subjects were educators teaching CSN at the school. The findings reveal that most teachers do not have a background in special education, but rather come from other disciplines such as mathematics, religion, physical education, and the arts. This lack of specialized training affects the accuracy of assessment practices, as teachers struggle to identify the individual needs of CSN comprehensively. The study underscores the urgent need for targeted training programs to equip non-specialist educators with adaptive assessment skills. The main contribution of this research lies in highlighting the importance of strengthening assessment competencies among general educators within the context of inclusive education, as a strategic step toward improving the quality of educational services for children with special needs. Keywords: assessment mechanism, educators in special schools, children with special needs